Charged Controlled Mem-Element Emulator and Its Application in a Chaotic System - Pankaj Kumar Sharma; Rajeev Kumar Ranjan; Fabian Khateb; Montree Kumngern (My University, 2020)
This article proposes a charged controlled emulator model for memristor and memcapacitor using second-generation Current Conveyor (CCIIs) and Analog Multiplier (AM). The grounded and floating mem-element circuits have been designed using two CCIIs and one multiplier in addition to some passive components. The grounded type of design requires three resistors and three capacitors while floating design necessitates only two resistors and two capacitors. With the help of a switch, the proposed design can be easily switched into a memristor or memcapacitor. The proposed emulator model has been theoretically analyzed and simulated in PSpice to substantiate the effectiveness and accuracy. The practicability of the circuit has been established using commercially available ICs AD844AN and AD633JN. Non-linear characteristics of the proposed memristor emulator have been used to design a chaotic system.
Keywords: Current conveyor; Memristor; Advanced Memory and Neural Computing